Study on growth and fecundity rate of eudrilus eugeniae in different ratios of soil, cow dung and newspaper - Tan, Yi Fie (2014)
Vermicompost is. product which produced from the interaction between earthworm and microorganisms by accelerating the biological degradation of organic wastes. Vermicomposting is an odourless and cost-effective process which produces nutrient rich organic fertiliser. This study is to compare the effects of soils on growth rate and fecundity rate of Eudrilus eugeniae as well as to compare the parameters of the worms by feeding with different ratios of cow dung and newspaper in soiled and soilless condition. It was carried out for 61 days or two months for composting process and the data was collected at weekly interval. The findings in this study concluded that soil gives no influences to the growth rate and reproduction rate of Eudrilus eugeniae in feeding mixture of cow dung and newspaper. By comparing the samples with treatment 4 in soiled and soilless condition, the growth rate of the worms was recorded higher in soiled-condition. This is due to the presence of soil microorganisms in contributing to the decomposition process of the feeding materials. The earthworms in samples with treatment 2 and treatment 3 recorded statistically significant higher reproduction rate than other treatments regardless the presence of soil.